2021
DOI: 10.2147/hmer.s333980
|View full text |Cite|
|
Sign up to set email alerts
|

The Prognostic Values of Neutrophil-to-lymphocyte Ratio and Platelet-to-Lymphocyte Ratio at Baseline in Predicting the In-hospital Mortality in Black African Patients with Advanced Hepatocellular Carcinoma in Palliative Treatment: A Comparative Cohort Study

Abstract: Background:The prognostic values of the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) in predicting the in-hospital mortality of Black African patients with advanced hepatocellular carcinoma (HCC) in palliative treatment is unknown. Aim: To determine the prognostic value of NLR and PLR compared with that of Child-Turcotte-Pugh (CTP), model for end-stage liver disease (MELD) scores and the Barcelona clinic liver cancer staging system (BCLC). Methods: The cutoffs, accuracies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…We attempted to develop a prognostic nomogram that combines most of the important serum markers and clinicopathological characteristics. Many studies have shown that carbohydrate antigen 199 and AFP are related to the OS of patients with HCC[ 18 , 19 ], and the NLR and PLR levels found in the current investigation were similar to earlier results[ 20 , 21 ]. However, we discovered that hematological markers such as NLR, and AFP were not predictive of DFS.…”
Section: Discussionsupporting
confidence: 92%
“…We attempted to develop a prognostic nomogram that combines most of the important serum markers and clinicopathological characteristics. Many studies have shown that carbohydrate antigen 199 and AFP are related to the OS of patients with HCC[ 18 , 19 ], and the NLR and PLR levels found in the current investigation were similar to earlier results[ 20 , 21 ]. However, we discovered that hematological markers such as NLR, and AFP were not predictive of DFS.…”
Section: Discussionsupporting
confidence: 92%
“…Owing to chronic infection with HBV or hepatitis C virus (HCV), patients with HCC and high NLR grade have neutrophilic leukocytosis and lymphocytopenia, which demonstrated that the balance is tilted towards tumor inflammatory response, leading to a disappointing surgical outcome. Previous studies have shown that NLR is independently associated with postoperative complications and in-hospital mortality (26,27). In our present study, similarly, we also confirmed that NLR is an independent risk factor for TO, suggesting the potential usefulness of deducing elevated NLR before LLR.…”
Section: Discussionsupporting
confidence: 90%
“…To assess the quality of the included trials, basic data were extracted, as shown in Table 1 . Of the 16 trials, 15 were in East Asia and the remaining 1 was in West Africa ( 43 ), including 11 in mainland China ( 34 , 37 , 39 41 , 44 , 46 50 ), 1 in South Korea ( 38 ), 2 in Taiwan ( 33 , 51 ), and 1 in Japan ( 36 ). All studies are from single-center clinical trials between 2012 and 2022.…”
Section: Resultsmentioning
confidence: 99%